GAMBARAN SEL RADANG AKUT DAN SEL RADANG KRONIK PADA HEMOROID INTERNA Berdasarkan Gambaran Histopatologi Pasien Hemoroid di Laboratorium Patologi Anatomi RSUD Ulin Banjarmasin Tahun 2017-2021 - Al Hasani, Siti Atthahirah; Oktaviyanti, Ika Kustiyah; Rosida, Lena; Wibowo, Agung Ary; Ulfah, Maria (Homeostasis, 2023)
Hemorrhoids are dilation and inflammation of the veins in the anus from the hemorrhoidal plexus. Based on histopathological characteristics, hemorrhoids are divided into internal, external and mixed hemorrhoids. Hemorrhoids become inflamed when they experience supporting tissue degeneration, which is divided into acute and chronic inflammation. The study aims to describe acute inflammatory cells and chronic inflammatory cells in internal hemorrhoids at the Anatomical Pathology Laboratory of Ulin Hospital, Banjarmasin, 2017-2021. This study used a descriptive observational method with a cross sectional approach through secondary data collection, using a total sampling technique. Of the 24 preparations, 20 samples (83.33%) showed acute inflammatory cells. In addition, chronic inflammatory cells were found in all samples. In the categorization of chronic inflammatory cells, the highest degree of chronic inflammatory cells was shown, namely moderate degrees of 14 samples (58.33%), 7 samples (29.17%) of severe chronic inflammatory cells, and 3 samples (12.5%) of chronic inflammatory cells. light degree. So it can be concluded that chronic inflammatory cells are found more frequently than acute inflammatory cells.